LEARNING MODEL OF RELIGIONS BASED ON THE QURAN TO IMPROVE RELIGIOUS MODERATION OF UPI STUDENTS - Firdaus, Endis; Rahmat, Munawar (Universitas Pendidikan Indonesia, 2021)
Abstrak: Penelitian ini bertujuan untuk menguji keefektifan model pembelajaran berbasis Al-Qur’an pada mata pelajaran agama untuk meningkatkan moderasi beragama siswa. Metode penelitian yang digunakan adalah research and development (RD). Hasil penelitian iii menunjukkan bahwa setelah mengikuti pembelajaran ini, sebagian besar siswa tidak mengaitkan Iman dan Kafir dengan identitas agama. Mereka mengatakan bahwa Iman dan keraguan berhubungan dengan akhlak yang baik dan buruk. Non-Muslim yang rendah hati, berakhlak mulia dan peduli menghilangkan beban manusia diangkat sebagai orang beriman oleh Allah. Sedangkan umat Islam yang angkuh, berakhlak buruk, dan egois dinilai kafir oleh Allah. Mereka juga akan mengizinkan pemeluk agama lain untuk melakukan kegiatan keagamaan dan mendirikan rumah ibadah di sekitar mereka. Dalam politik praktis, mereka rela memilih calon pemimpin terbaik meski agama mereka non-Muslim. Kata kunci: Model pembelajaran, Al-Qur’an, Moderasi agama, Moderasi Abstract: This study aims to examine the effectiveness of the Qur'an-based learning model on religious subjects to increase students' religious moderation. The research method used is research and development (RD). The results of this study show that after following this lesson, most of the students did not associate Faith and Kafir with religious identity. They say that Faith and doubt are related to good and bad morals. Non-Muslims who are humble, have noble character and care about removing human burdens are appointed as believers by Allah. Meanwhile, Muslims who are arrogant, have bad morals, and are selfish are considered infidels by Allah. They will also allow followers of other religions to carry out religious activities and build houses of worship around them. In practical politics, they are willing to choose the best candidate for leader even though their religion is non-Muslim.Keywords: Learning model, Al-Qur'an, Religious moderation, Moderation